Pirates don't change diapers - Long, Melinda (Harcourt, Inc., 2007)
Braid Beard and his pirate crew return to retrieve the treasure they buried in Jeremy Jacob's backyard, but first they must help calm his baby sister, Bonney Anne, whom they awoke from her nap.